SISTEM INFORMASI PEMANTAUAN KINERJA PROSES PRODUKSI PERCETAKAN DIGITAL DENGAN METODE BALANCE SCORECARD (STUDI KASUS PT. SUMSEL SARANA SEMESTA PALEMBANG) - Nining Ariati; Suzan Agustri (Jurnal Informatika Global)
The  number  of digital  printing  of customer's  order  requires  PT . Palembang South Sumatra Universe Means to improve services in order processing and production , but sometimes  appear some problems  in the production  process  such as the difficulty  of monitoring  the performance  of a production  process that causes errors and delays in orders in the production process , thereby reducing the level of customer satisfaction on the performance of the company's production uncollectible accounts and the number of customers that are difficult to be seen by the companies that caused the financi al loss . This  study  uses  the  Balanced  Scorecard  methodology  of research, which  include  : financial perspective,  customer,  internal  business  processes  and  innovation  and learning. This research aims to create an information system performance monitorin g production  process  of digital printing  with  the Balanced  Scorecard method  that will help  improve  the  performance  of  the  entire  production process,  including  checks related  to  doubtful  accounts,  customer satisfaction   with  the  order  process  and production performance as well as help management to monitor the performance of the process digital printing production.Keywords : monitoring performance , balance scorecard , digital printing